2020
DOI: 10.3390/electronics10010064
|View full text |Cite
|
Sign up to set email alerts
|

Signal Detection Based on Power-Spectrum Sub-Band Energy Ratio

Abstract: The power-spectrum sub-band energy ratio (PSER) has been applied in a variety of fields, but reports on its statistical properties and application in signal detection have been limited. Therefore, the statistical characteristics of the PSER were investigated and a signal detection method based on the PSER was created in this paper. By analyzing the probability and independence of power spectrum bins, as well as the relationship between F and beta distributions, we developed a probability distribution for the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In practice, the doubly non-central beta or F distributions are widely used. Li et al [2] confirmed that in the presence of a signal, the detection statistic, that is, the power spectrum sub-band energy ratio, conforms to the doubly non-central beta distribution. Giner-Bosch et al [3] confirmed that the multivariate coefficient of variation used in monitoring obeys the singly non-central F distribution, which is a special case of the doubly non-central F distribution.…”
Section: Introductionmentioning
confidence: 93%
“…In practice, the doubly non-central beta or F distributions are widely used. Li et al [2] confirmed that in the presence of a signal, the detection statistic, that is, the power spectrum sub-band energy ratio, conforms to the doubly non-central beta distribution. Giner-Bosch et al [3] confirmed that the multivariate coefficient of variation used in monitoring obeys the singly non-central F distribution, which is a special case of the doubly non-central F distribution.…”
Section: Introductionmentioning
confidence: 93%
“…The signal-to-noise ratio (SNR) is a regularly used process to evaluate the quality of a signal and estimate the influence of noise on a signal. In this process, the power ratio of the signal power to the total noise is estimated by the spectral data [20], [21]. In fast Fourier transform (FFT), the captured waveform data samples will be transformed into the frequency domain where the captured signal will be in the form as shown in (1).…”
Section: Signal To Noise Ratiomentioning
confidence: 99%
“…That is, a discrete signal X[n] decomposition can be presented as in (7). followed by a down-sampling by two driven by mother wavelet and the scaling function [20], [21], [28], as shown in Figure 1, which makes DWT suitable for signal analysis with fewer data samples and particularly for transient signals. However, in this work, instantaneous amplitude measurements and waveform dynamic range will be based on the low-pass approximation coefficients to eliminate noises and obtain an accurate reading.…”
Section: Wavelet Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…Power Spectrum Analysis has been a major tool to detect particular characteristics of the event(s), including amplitudes, energy ratio, frequency, noise, correlation, probability density, cumulative distribution function, etc. occurred in the recorded signal from different sources through the Fast Fourier Transform (FFT) 8 . The relevant statistical signal analysis aspects have been applied to detect single nanoparticles and biological molecules such as yeast ribosomes floating in fluids exposed to laser beams 9 .…”
Section: Introductionmentioning
confidence: 99%